Self-Disclosure in Toxic Relationship in Victims of Affairs Under the Suspicion of Rifka Annisa Foundation - Utomo, Ardian Setio; Harjo, Feysa Evina Sugih; Widhihatmini, Widhihatmini (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2025)
Infidelity can occur due to a lack of quality interpersonal communication between partners. This study aims to analyze communication patterns in toxic relationships and how communication is used as a strategy in dealing with infidelity in victims of infidelity who are under the auspices of the Rifka Annisa Foundation. The theory used in this study is the theory of relationship stages, where relationships occur gradually, moving from initial contact to deeper intimacy and sometimes even shifting to damage. This study uses a qualitative approach. Data collection was carried out through documentation, observation, and in-depth interviews with six people. In this study, data analysis was carried out interactively. The results of the study found that self-disclosure plays an important role in the stages of toxic relationships. However, if there is a decrease in self-disclosure, it can lead to potential conflict and injustice. Self-disclosure is related to the victim's perception of injustice in understanding the complexity of interpersonal conflict because interpersonal communication built between partners tends to be manipulative, and responses to infidelity vary, including proactive efforts to improve relationships, focus on self-well-being, seek help from a counselor and break off relations with a partner.Keyword: Interpersonal Communication, Relationship Stages, Self-Disclosure, Toxic RelationshipABSTRAKPerselingkuhan dapat terjadi akibat kurangnya kualitas komunikasi interpersonal antara pasangan. Penelitian ini bertujuan untuk menganalisis pola komunikasi dalam hubungan toksik dan bagaimana komunikasi digunakan sebagai strategi dalam menghadapi perselingkuhan pada korban perselingkuhan yang berada di bawah naungan Yayasan Rifka Annisa. Teori yang digunakan dalam penelitian ini adalah teori tahapan hubungan, dimana hubungan terjadi secara bertahap, bergerak dari kontak awal menuju keintiman yang lebih dalam dan terkadang bahkan bergeser ke arah kerusakan. Penelitian ini menggunakan pendekatan kualitatif. Pengumpulan data dilakukan melalui dokumentasi, observasi, dan wawancara mendalam terhadap enam orang. Dalam penelitian ini, analisis data dilakukan secara interaktif. Hasil penelitian menemukan bahwa pengungkapan diri memegang peranan penting dalam tahapan hubungan toksik. Namun, apabila terjadi penurunan pengungkapan diri, maka dapat menimbulkan potensi konflik dan ketidakadilan. Pengungkapan diri terkait dengan persepsi korban tentang ketidakadilan dalam memahami kompleksitas konflik interpersonal karena komunikasi interpersonal yang dibangun antara pasangan cenderung manipulatif, dan respons terhadap perselingkuhan bervariasi, termasuk upaya proaktif untuk meningkatkan hubungan, fokus pada kesejahteraan diri, mencari bantuan dari konselor dan memutuskan hubungan dengan pasangan.Kata Kunci: Komunikasi Antarpribadi, Tahapan Hubungan, Pengungkapan Diri, Hubungan Beracun